Developing Malaysia's smart community-based tourism model / Azila Azmi and Johanna Adlin Ahmad - Azmi, Azila; Ahmad, Johanna Adlin (Universiti Teknologi MARA, Perlis, 2022)
Smart tourism is a 21st-century technological phenomenon where tourism suppliers and tourists are interconnected. The Malaysia National Tourism Policy's 2020-2030 concurs that one of the tactical strategies to increase visitor's economy in the rural areas is through 'digitalization'. Parallel to this, community-based tourism's (CBT) homestay programs have long been a government's endeavor in assisting rural tourism's economics. In heading towards smart tourism, CBT must be consistent with the progress. However, current investigation on CBT's readiness to accept smart tourism in Malaysia is still infancy. This is a proposed study with objectives to explore the concept of smart CBT within the Malaysian context, to investigate the readiness of CBT in Malaysia to adopt smart tourism, and to identify the strategies for Malaysia National Tourism Policy. The study will employ qualitative approach where semi-structured interview will be conducted with industry experts associated with tourism and homestays from different regions in Malaysia. The expected findings will establish the current setting of smart tourism in the CBT context, which will derive input for Malaysia National Tourism Policy.